Pemanfaatan Kotoran Ayam Sebagai Pupuk Organik Padat Untuk Peningkatan Kualitas Tanaman di SMA Negeri 1 Gunung Sari - Rachmawati Noviana Rahayu; Immy Suci Rohyani; Ernawati Ernawati; Isrowati Isrowati; Dela Savira (Universitas Mataram, 2023)
Land potential in the West Nusa Tenggara region can still continue to be developed for various types of crops where the use of organic matter can support land productivity. The abundant amount of livestock waste availability, especially chickens, can be used as solid organic fertilizer. Socialization activities in the school environment of SMA Negeri 1 Gunung Sari are implementation activities aimed at improving plant quality by utilizing chicken manure as solid organic fertilizer. This activity takes place through several stages, namely the preparation stage and the preparation of material, implementation stage accompanied by workshop activities with Direct Instruction and Focus Group Discuss and demonstration stage of making and applying organic fertilizer chicken manure in the environment around the school. The output of this activity is expected to increase awareness for workshop participants to be able to protect the surrounding environment by processing chicken manure waste to be used as planting media that can trigger plant growth and development, so as to reduce the rate of use of inorganic fertilizers that can reduce land quality.